2009
DOI: 10.3390/s91210136
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing and Skywave Digital Communication from Antarctica

Abstract: This paper presents an overview of the research activities undertaken by La Salle and the Ebro Observatory in the field of remote sensing. On 2003 we started a research project with two main objectives: implement a long-haul oblique ionospheric sounder and transmit the data from remote sensors located at the Spanish Antarctic station Juan Carlos I to Spain. The paper focuses on a study of feasibility of two possible physical layer candidates for the skywave link between both points. A DS-SS based solution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In this paper we compare the behavior of different transmission schemes based on DSSS and OFDM techniques, and we present some conclusions that derive from the data gathered during the 2010/2011 and 2011/2012 Antarctic surveys. Previous results [ Bergadà et al , ] showed preliminary conclusions supported on a reduced frequency and time range.…”
Section: Test Designmentioning
confidence: 80%
“…In this paper we compare the behavior of different transmission schemes based on DSSS and OFDM techniques, and we present some conclusions that derive from the data gathered during the 2010/2011 and 2011/2012 Antarctic surveys. Previous results [ Bergadà et al , ] showed preliminary conclusions supported on a reduced frequency and time range.…”
Section: Test Designmentioning
confidence: 80%
“…The typical pattern of the summer behavior of the ionospheric F2 characteristics and of their variability was evaluated for different Spanish Antarctic surveys, and the differences of the above patterns from survey to survey were related to the different solar activity [54]. Such a pattern at mid-high latitudes of the ASJI was also compared with the summer behavior at other mid-latitude stations and it was noticed a larger post-sunset electron density enhancement at the ASJI than that recorded in other regions.…”
Section: Vertical Ionospheric Soundingmentioning
confidence: 99%
“…The system was designed to satisfy a project born in 2003 with a double objective: to transmit the data from remote sensors located at the Spanish Antarctic Station Juan Carlos I directly to Spain but implementing a long-haul oblique ionospheric sounder also. For more details on the system we refer the reader to [14,15].…”
Section: System Descriptionmentioning
confidence: 99%